The Demand for Labor - Monroe, A. E. (Quarterly Journal of Economics, 1933)
I. Marginal productivity ignores important forms of investment, 627; and is inaccurate even for "productive" investment, 628.— The "law" of diminishing productivity vague and subject to serious exceptions, 630.— Marshall's doctrine of marginal net product does not explain general wages, 631; but throws light on the process of equilibrium-seeking, 632.— The application of labor to land, 633.— II. "Demand for labor" a misleading expression, 634.— Factors which determine it, 635.— The "method of increments" not involved, 638.— In what sense wages are residual, 639.— III. Practical implications: for changes in working hours, 640; consumer borrowing, 641; raising of wages above equilibrium rate, 642; elasticity of demand for labor, 643.